ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP KELELAHAN KERJA BAGIAN WELDER DI PT KTU SHIPYARD TANJUNG RIAU: Fatigue; Noise; Temperature; Welder; Working environment. - zico, zico fahlevy; Zetli, Sri (Computer Science and Industrial Engineering, 2026)
Welding activities at PT KTU Shipyard Tanjung Riau are carried out in a work environmentwith relatively high exposure to heat and noise, which may potentially cause work fatigueamong welders. This study aims to determine the working environment conditions in termsof temperature and noise levels, analyze the level of work fatigue. The research method wasconducted through measurements of temperature and noise levels in the work area. Theresults showed that the working area temperature obtained an average score of 33 with apercentage of 66%, and the noise level obtained an average score of 31.6 with a percentageof 63%, indicating that welders were exposed to heat and noise conditions. The level of workfatigue was in the moderate category with an average score of 78.8 and a percentage of53%. The results of multiple linear regression analysis showed that the working areatemperature did not have a significant effect on work fatigue with a significance value of0.904 (> 0.05), while the noise level had a significant and positive effect on work fatigue witha significance value of 0.0001 (< 0.05). Therefore, noise level is the dominant factor affectingwork fatigue among welders.